EVALUASI PENERAPAN PROSEDUR PENGIRIMAN BARANG PADA SISTEM PENJUALAN DALAM UPAYA MENINGKATKAN PERSPEKTIF KONSUMEN DI PERUSAHAAN EXPEDISI - KHOLID, AHMAD (Jurnal Akuntansi AKUNESA, 2018)
The purpose of this study is to understand the application of delivery procedures on goods sales system in an effort to increase customer satisfaction. This research uses descriPT.ive qualitative method and uses direct field observation approach on PT. Tridominic Surabaya, data was colected by interview with leaders, employees, and some documents in the form of delivery work report to know the data delivery and the type of research is case study. The finding on this research appear that the customer of PT. Tridominic Surabaya have enough satisfied with the condition and quality of service at time. This is based on research results that this factor has the highest satisfaction value of the company that has implemented the process of delivery of goods, internal control and procedures in accordance with the demand but there is lack of monitoring the contents turnover of container box towards condition of the process of goods delivery caused by loading of irregular cargo, resulting in decreased income.